2019
DOI: 10.14738/assrj.64.6457
|View full text |Cite
|
Sign up to set email alerts
|

Digital Divide, Digital Inclusion and Inclusive Education

Abstract: Digital divide refers to the gap of unequal accessibility and experience for access and use of modern information and communication technologies; digital inclusion has a focus on a practical, policy-driven approach in this context that addresses the needs of communities as a whole. Inclusive education is a process of strengthening the capacity of education systems to reach out all learners being welcomed in regular classes and to support them to learn, contribute and participate in all aspects of the life in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 3 publications
0
15
0
5
Order By: Relevance
“…Researchers have suggested that combining technology tools with teachers' capabilities will solve the problem of inequality in the education system especially in the emerging context (Srivastava & Shree, 2019). It has been shown that to manage this digital transformation needed in schools, there is also need for the adoption of a new strategy of education (Hamburg, 2019). Researchers have shown that inclusive development is often guided by fighting against poverty and the promotion of inclusive education .…”
Section: Literature Review 21 Inclusive Education As a Sustainable Dmentioning
confidence: 99%
“…Researchers have suggested that combining technology tools with teachers' capabilities will solve the problem of inequality in the education system especially in the emerging context (Srivastava & Shree, 2019). It has been shown that to manage this digital transformation needed in schools, there is also need for the adoption of a new strategy of education (Hamburg, 2019). Researchers have shown that inclusive development is often guided by fighting against poverty and the promotion of inclusive education .…”
Section: Literature Review 21 Inclusive Education As a Sustainable Dmentioning
confidence: 99%
“…It is necessary to abandon this concept and expand the view in order to model a holistic picture of the audience of distance education [21]. Therefore, the development of inclusive education is a step towards the future where everyone will have equal opportunities for self-realization [22].…”
Section: Discussionmentioning
confidence: 99%
“…This shows the fact in the study that AA's agency in learning is attained and well-performed. Previous studies negatively undermined gifted student' learning performance [7], [19], [50], and this might contribute to students' underachievement [42].…”
Section: Student's Sustained Participation In the Inclusive Educationmentioning
confidence: 96%